Analisis Motivasi Pelanggan dalam Membentuk Minat Beli Produk Melalui Fitur Shopee Live - Buntoro, Cynthia; Hartanti, Lisa Esti Puji (School of Communication - Atma Jaya Catholic University of Indonesia, 2024)
This research aims to analyze customer motivation in shaping product purchase intention through the Shopee Live feature. The method used in this research is descriptive qualitative, with data collected through Focus Group Discussion (FGD). The informants in this research are Shopee Live customers aged 20-25 years old who live in Jakarta. Other methods used include Shopee Live platform observation and literature studies. The result of this research identifies four main customer motivations in shaping product purchases. First, the ease of transaction processes in establishing new relationships between sellers and buyers through e-commerce features. Second, product, price, and service factors that motivate customer to make purchases. Third, purchase satisfaction is achieved by fulfilling needs according to the customer’s personality, perception, and attitude. Fourth, communication that attracts attention to social commerce content can increase the desire to purchase.